On the type selection and re-typification of two monitor lizard taxa (Squamata: Varanidae): Monitor bivittatus celebensis Schlegel, 1844 and Monitor kordensis Meyer, 1874; with some comments and corrections on other name-bearing type specimens - Böhme, Wolfgang; Koch, André (Zootaxa, 2010)
We comment on a recently published checklist of the extant monitor lizards (Varanidae) by De Lisle (2009) which aimed also to give the repositories and catalogue numbers of name-bearing type specimens. In two out of 28 cases (i.e., Monitor bivittatus celebensis Schlegel, 1844 and Monitor kordensis Meyer, 1874) where the onomatophores could not be traced, he decided to designate a lectotype and a neotype, respectively, which, however, was not in accordance with the International Code of Zoological Nomenclature (ICZN). Therefore, we regard these designations as invalid and discuss and clarify the status of further type material listed by De Lisle (2009). Moreover, we make some additional corrections in his list.